Algunas aplicaciones de los plásticos en las industrias del empaque y automotriz - Guerrero Salazar, Carlos Alberto; González González, Virgilio Ángel (UANL. Facultad de Ingeniería Mecánica y Eléctrica, 2002)
The role of plastic materials in the packaging and automotive industries is commented. Specific applications such as poly(ethylene-terephtalate) as gas barrier on the soft-drink bottle industry and low density polyethylene on the flexible packaging industry are presented. The use of polypropylene, high density polyethylene and polyamides are also mentioned.